An Incentive Mechanism to Break the Low-skill Immigration Deadlock - David de la Croix; Frederic Docquier (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
Although movements of capital, goods and services are growing in importance, workers movements are impeded by restrictive policies in rich countries. Such regulations carry substantial economic costs for developing countries, and prevent global inequality from declining. Even if rich countries are averse to global inequality, a single country lacks incentives to welcome additional migrants as it would bear the costs alone while the benefits accrue to all rich states. Aversion to global inequality confers a public good nature to the South-North migration of low-skill workers. We propose an alternative allocation of labor maximizing global welfare subject to the constraints that the rich countries are at least as well off as in the current "nationalist" (or "Nashionalist") situation. This "no regret" allocation can be decentralized by a tax-subsidy scheme which makes people internalize the fact that as soon as a rich country welcomes an additional migrant, global inequalities are reduced, and each citizen in the rich world is better off too. Our model is calibrated using statistics on immigration, working-age population and output. We simulate the proposed scheme on different sets of rich countries.
Keywords: F22; F55; D58; D6; D7; 330; Public Good; Inequality Aversion; Immigration policy